CONTRIBUTORY ROLE OF RESTAURANT SERVICES IN THE GROWTH OF NIGERIA’S HOSPITALITY INDUSTRY (Journal of the Management Sciences, 2025)
The contributory role of restaurant services in the growth of the hospitality industry is a vital area of focus, particularly in Nigeria's evolving service economy. This study investigates how restaurant services impact the broader hospitality sector, with emphasis on their influence on tourism, employment, local economies, and guest satisfaction. Using a desk review research approach, secondary data were drawn from scholarly articles, online journals, industry reports, and case studies in Nigeria and comparable contexts, including evidence from global best practices, the study explores the interaction between restaurant operations and other hospitality segments such as hotels and event centers. The research also analyzes how innovation, sustainability, and customer preferences drive service improvement in restaurants. Findings reveal that restaurant services significantly enhance customer retention, promote cultural tourism, and contribute to revenue generation and employment. The study concludes that advancements in restaurant service delivery are closely linked to the competitiveness and growth of the Nigerian hospitality industry.
Keywords: Restaurants; Hospitality Industry; Fine Dining; Food And Beverage; Customer Satisfaction